2024
DOI: 10.1039/d4ob00608a
|View full text |Cite
|
Sign up to set email alerts
|

Lewis acid catalyzed Markovnikov hydrobromination and hydrochlorination of alkynes using TMSX (X = Br, Cl)

Dalong Shen,
Dehai Cao,
Ruizeng Zhang
et al.

Abstract: The Markovnikov hydrobromination and hydrochlorination of alkynes were achieved using TMSX (X = Br, Cl) instead of corrosive HX (X = Br, Cl) as the bromination and chlorination reagents. Mn(OAc)2.4H2O...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Recently, we achieved the hydrobromination and hydrochlorination of alkynes in the presence of Mn(II) and Zn(II) catalysts. 16 Herein, we would like to report our findings on the Mn(II)catalyzed hydroiodination reaction of terminal aryl alkynes. The current methodology featured the cheap Mn(II) catalyst, mild conditions, and gram-scale synthesis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we achieved the hydrobromination and hydrochlorination of alkynes in the presence of Mn(II) and Zn(II) catalysts. 16 Herein, we would like to report our findings on the Mn(II)catalyzed hydroiodination reaction of terminal aryl alkynes. The current methodology featured the cheap Mn(II) catalyst, mild conditions, and gram-scale synthesis.…”
mentioning
confidence: 99%
“…In our previous hydrohalogenation reactions using TMSX (X = Br, Cl), we found that the choice of Lewis acid catalyst was based on both the Lewis acidity of TMSX and the electronic factors of substrates. 16 For electron-neutral/rich alkynes, Mn(OAc) 2 •4H 2 O was the hydrobromination catalyst. For hydrobromination of electron-deficient alkynes and hydrochlorination of alkynes, Zn(OAc) 2 •2H 2 O was employed as the catalyst.…”
mentioning
confidence: 99%
See 1 more Smart Citation